Development Model of Elderly Clubs in Chiang Mai Province - ศรีบุญเรือง, อนงค์ (Community and Social Development Journal, 2018)
The qualitative research, Development Model of Elderly Clubs in Chiang Mai Province, have purpose to study the development and effects from the development of elderly clubs in Chiang Mai by the application of community based research, action research and participatory rural appraisal. The research, that studied 38 elderly clubs in Chiang Mai, used structural in-depth interviews to collect datas from 456 people consist of chairmans, committees, members and networks since 2559 to 2560. The results of this research are 1) the development of elderly clubs in Chiang Mai, that established within communities, has got supporting like mentoring system from government agencies. Their activities have been essentially exercise and recreation. Also, they have had the planning, processing and easily monitoring. They have brought their collected datas and performance of club activities to conclude and explain to their members periodically. Consequently, they have used technology to explicate and distribute informations and news efficiently. Their development started from families that gather together as a communities and have created networks among the groups into the Digital Society. 2) the effects from the development of elderly clubs in Chiang Mai have led participation of community leaders and members in sharing their opinions, that make everyone to work with willing. The activities of this research, that have initiatives and learning together in the "We can do it by Anong" model, have influence factors as follows: 1) Willing 2) Exploration 3) Cognition 4) Action 5) Notice 6) Decoration 7) Outstanding 8) Interesting 9) Team in technology 10) Again 11) New 12) Opinion 13) Natural and 14) Good will.